ANALISIS KEMAMPUAN BERPIKIR REFLEKTIF MATEMATIS SISWA PADA MATERI STATISTIKA DITINJAU DARI SELF-REGULATED LEARNING - Risda Putri Nugrahani; Adi Nurcahyo; Muhammad Noor Kholid (Jurnal Lebesgue : Jurnal Ilmiah Pendidikan Matematika, Matematika dan Statistika, 2024)
Students need to have the ability to think in order to solve a problem from the problem at hand. This study aims to describe the reflective thinking ability of seventh grade students of SMP Batik Surakarta when they solve problems involving statistics in terms of Self-Regulated Learning. This research used qualitative research method with descriptive research type. The subjects in this study were students of class VII C SMP Batik Surakarta. Data collection begins with filling out a self-regulated learning questionnaire by students and reflective thinking ability test questions then from the results of the categorisation based on the results of the questionnaire conducted interviews. The results of this study are students who have self-regulated learning with high category have high reflective thinking ability can fulfil the indicators of reflective thinking reacting, comparing, and contemplating. Students who have moderate self-regulated learning have moderate reflective thinking ability can fulfil two indicators of reacting, and comparing. Students who have low self-regulated learning category have less reflective thinking ability that only fulfils one reflective thinking indicator which is reacting